Macroscopic Response and Decohesion Models of Metal-Polymer Laminates - Gabriella BOLZON; Mahdieh SHAHMARDANI (Engineering Transactions, 2017)
Metal-polymer laminates are used in several technological fields, with applications ranging from flexible electronics to food packaging and lightweight components for transportation sectors. Models of different complexity have been proposed to evaluate the overall performances of these materials. Models are also used to recover the adhesion properties of the plies, which are difficult to be characterized otherwise. The overall material responses resulting from different constitutive assumptions are examined in this paper.